Ammonium nitrate explosives for civil applications : slurries, emulsions and ammonium nitrate fuel oils - Mahadevan, Erode G.; Wiley eBooks (Weinheim : Wiley, 2013)
The book describes the science and technology of formulation and manufacturing of non-nitroglycerine explosives with ammonium nitrate as the main ingredient. Based on the author's industry experience of more than thirty years, it provides an unparalleled treatment of one of the commercially most important classes of explosives and therefore stimulates further research and development efforts in the field of explosives for civil applications.
Classification of Explosives -- Explosive Science -- Ammonium Nitrate Explosives -- Ammonium Nitrate and AN/FO -- Slurries and Water Gels -- Emulsion Explosives -- Research and Development -- Functional Safety During Manufacture of AN Explosives -- Economics of AN-Based Explosives -- Current Status and Concluding Remarks -- Appendix A -- Appendix B: Guidelines for Investigation of an Accident.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Ammonium nitrate fuel oil; Ammonium nitrate; Mine gases; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Ammonium nitrate; Ammonium nitrate fuel oil; Electronic books